2016
DOI: 10.1007/s12035-016-9796-3
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Endogenous Resistance of Brain to Ischemia

Abstract: Most survivors of ischemic stroke remain physically disabled and require prolonged rehabilitation. However, some stroke victims achieve a full neurological recovery suggesting that human brain can defend itself against ischemic injury, but the protective mechanisms are unknown. This study used selective pharmacological agents and a rat model of cerebral ischemic stroke to detect endogenous brain protective mechanisms that require activation of α7 nicotinic acetylcholine receptors (nAChRs). This endogenous prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 69 publications
(170 reference statements)
2
28
0
Order By: Relevance
“…In contrast, blockade of α7nAChRs with the selective antagonist, methyllycaconitine, increased infarct size, suggesting some degree of α7 stimulation by endogenous agonist (Han et al 2014). Other investigators have suggested that endogenous choline that is released from injured brain tissue might fill this role (Sun et al, 2013a; Sun et al, 2017). These investigators found that treatment with PNU-120596, an allosteric modulator of α7nAChRs, decreased infarct size and improved performance on several neurological tests when given 6 h after transient occlusion of the middle cerebral artery in mice (Sun et al, 2013a).…”
Section: Targeting α7nachrs On Microglia and Macrophages In Strokementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, blockade of α7nAChRs with the selective antagonist, methyllycaconitine, increased infarct size, suggesting some degree of α7 stimulation by endogenous agonist (Han et al 2014). Other investigators have suggested that endogenous choline that is released from injured brain tissue might fill this role (Sun et al, 2013a; Sun et al, 2017). These investigators found that treatment with PNU-120596, an allosteric modulator of α7nAChRs, decreased infarct size and improved performance on several neurological tests when given 6 h after transient occlusion of the middle cerebral artery in mice (Sun et al, 2013a).…”
Section: Targeting α7nachrs On Microglia and Macrophages In Strokementioning
confidence: 99%
“…These investigators found that treatment with PNU-120596, an allosteric modulator of α7nAChRs, decreased infarct size and improved performance on several neurological tests when given 6 h after transient occlusion of the middle cerebral artery in mice (Sun et al, 2013a). Subsequent work demonstrated that intranasal administration of PNU-120596 had similar therapeutic efficacy using the same stoke model in rats (Sun et al, 2017).…”
Section: Targeting α7nachrs On Microglia and Macrophages In Strokementioning
confidence: 99%
“…Acetylcholine, via nicotinic receptors (nAChRs), is involved in hypoxic or ischaemic preconditioning in the brain and other organs, and this is most convincingly demonstrated for the homomeric α7 nAChRs [18][19][20][21]. The preconditioning (as well as postconditioning) α7 nAChRs effects are closely related to neuronal adaptive and neuroimmune antiinflammatory mechanisms in which α7 nAChRs are particularly important in protecting against hypoxic damage in peripheral organs [22][23][24][25] and the central nervous system [19,20,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous choline released from damaged brain tissue may fulfil this role. The use of an allosteric modulator of α7nAChRs 6 h after tMCAO can reduce the infarct volume and improve neurological performance [231, 232]. In addition, regulation of α7nAChRs has also been shown to be associated with changes in M1 and M2 microglia/macrophages after CI [229].…”
Section: Introductionmentioning
confidence: 99%